Strategi Pengelolaan Ekowisata Berbasis Masyarakat di Bukit Pergasingan, Desa Sembalun, Lombok Timur: Community-Based Ecotourism Management Strategy in Bukit Pergasingan, Sembalun Village, East Lombok - Baiq Jiwa Yulina Putri; Andi Chairil Ichsan; Andi Tri Lestari (Forestry Faculty of Hasanuddin University, 2023)
Bukit Pergasingan is a tourist attraction that has been developing for a long time. It is necessary to review essential aspects in the management of Bukit Pergasingan, such as attractiveness, facilities, accessibility, and additional services. Apart from that, another problem with its management is that it is not yet known whether it has implemented the principles of community-based ecotourism development in its management. This research aimed to determine community-based ecotourism management strategies in Bukit Pergasingan. The method used in this research is the descriptive method. The objects used in this research are the management institution (BKPH Rinjani Timur) and the management partner (Kelompok Koperasi Wisatani). The tools used in conducting this research were questionnaires, cameras, laptops, recorders, and stationery. The data used in this research are qualitative and quantitative. The data sources used in this research are primary data and secondary data. The data analysis used is SWOT analysis. The results of the research show that the strategies used for managing Ecotourism in the Bukit Pergasingan tourist attraction are socializing Bukit Pergasingan tourism with its potential by involving it to attract tourists, packaging more attractive and more educational tour packages related to conservation to guests, optimizing collaboration with NGOs, the Tourism Office or related agencies for the development of Bukit Pergasingan tourism.